Host plant-related responses on the thermal fitness of Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) - Mutamiswa, Reyard; Machekano, Honest; Nyamukondiwa, Casper; Chidawanyika, Frank (Springer, 2022)
Diet quality influences arthropod performance under changing environments. However, little is known about how host plant species may influence the responses of polyphagous insects to climate stressors despite their exploitation of different plant species within and across seasons. Against this background, we examined the effects of host plant species (Zea mays L. and Sorghum bicolor L. Moench) on the thermal tolerance of Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) measured as lower and upper thermal activity limits, chill coma recovery time and heat knockdown time. Experiments were conducted on field-collected larvae and laboratory-reared F1 larval offspring from each of the two host species. Our results showed significant host plant effects on both cold and heat tolerance. Insects from sweet sorghum showed higher thermal resilience (cold and heat) relative to those from maize as indicated by their low lower thermal activity limits (0.73 and 0.02 °C magnitude, respectively) and high upper thermal activity limits (0.5 and 0.28 °C magnitude, respectively). Both field and F1 larval populations from sweet sorghum recovered faster from chill coma and also took longer to be knocked down by acute heat stress, further affirming their superior thermal tolerance to those that fed on maize. These results therefore indicate that host plant species may potentially mediate thermal fitness of C. partellus. Despite wide adoption of sweet sorghum as a climate resilient crop owing to its drought tolerance and perennial nature, our findings suggest this may come at a cost of enhanced C. partellus performance and pest pressure under changing temperature environments.